Protection of Ten-Eyed Bridge in Diyarbakır - Karasin, Ibrahim; Isik, Ercan (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Mesopotamia, which is one of the strategical regions of the Middle East, has hosted numerous communities and civilizations since the ancient times of human history. This situation made the region considerably prosperous in terms of historical and cultural heritage. Ten-Eyed Bridge, that is one of the most important historical and cultural symbols of Diyarbakir, having lasted till today, became an example of this prosperous heritage. However, various interventions and deteriorations have occurred in the construction within long time due to the impact of human and nature. Because of the considerable temperature difference arising due to continental climate of the region as well as damages like the change of conditions of use, amortizations in bearing constructional components in contact with water have emerged. In this study, with the purpose of ensuring further future existence of Ten-Eyed Bridge, adopted methods for structural and physical deteriorations and protection works were examined.